MENINJAU MASALAH DAN MENCARI SOLUSI UNTUK TENAGA KERJA ANAK DI PERTAMBANGAN TIMAH BANGKA BELITUNG: MENGATASI TANTANGAN DIBALIK INDUSTRI PERTAMBANGAN - Zamzani, Zamzani; Mutholib, Abdul (DISCOURSE: Indonesian Journal of Social Studies and Education, 2024)
The phenomenon of social problems is considered to be an obstacle to the realization of social welfare. One of the social problems that occurs in the tin mining sector in Bangka Belitung is the prolonged exploitation of child labor. This situation must receive immediate attention so that there is no widespread impact. This research aims to describe and critically examine the background to the problem of exploitation of children in the tin mining of Bangka Belitung and to see what solutions are being implemented by the Gubuk Sejuta Motivasi Foundation in dealing with this problem. This type of research is qualitative-descriptive-analysis by describing field phenomena according to the reality that occurs in the field. To obtain data, researchers used interview, observation and documentation methods. The determination of informants was based on criteria, namely, 3 Foundation Management, 9 Mining Workers' Children and 3 people fostering children. The results of the study reveal that the problem of exploitation of children is caused by various problems. First, internal problems in children, namely, dropping out of education, early marriage, and child delinquency. Second, external problems, namely mining culture and traditions, the miner's environment, reasons for helping parents, weak parental education, and promising economic benefits. Based on field findings, as for the solution of the Gubuk Sejuta Motivasi Foundation in dealing with the problem of exploitation of tin worker children with several approaches. First, providing Soft Skills for children, in the fields of formal and non-formal education. Second, providing hard skills in the interests and talents of each child, some are in Gubuk Otomotif, Gubuk Seni, Gubuk Kayu, Bubuk Tani, and Gubuk Perikanan Viewed from a practical social science perspective, the approach taken by the Gubuk Sejuta Motivasi Foundation can be a reference and lesson for the parties responsible for social problems that continue to develop dynamically in society.